Działalność konspiracyjna Żydów w Krakowie jako reakcja na niemiecką politykę Zagłady - Zajączkowska-Drożdż, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
This article presents a detailed history of what the underground resistance of Krakow’s Jews consisted of during the Second World War. It incorporates examples of different types of passive resistance applied as well as the history of illegal organisations that undertook aid activities and Jewish partisan actions. The activities of the partisans in the Krakow forests is scrutinised, together with how contact networks and the production of illegal documents were organised. The article contains a comprehensive analysis of the greatest military achievement of Krakow Jews, known as “attack on Bohemia”, which was remembered as a momentous occasion. Finally, the article shows the evolution of the idea of resistance to the Germans and their anti-Jewish policy among Jewish youth.
Keywords: żydowska konspiracja; Kraków; opór zbrojny; getto krakowskie